Design and Build The Dokestrans Application For Document Management of The Perum Damri Safety Management System - Moh. Adam Asshofi; Joko Siswanto; Nurul Fitriani (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The Safety Management System (SMK) documents at the Public Transportation Company (PAU) Perum Damri are currently stored using Google Drive, leading to inefficiencies such as document loss, difficulty in locating specific files, and disorganized storage. These challenges hinder the effective compilation and management of SMK PAU documents, potentially impacting safety and compliance standards. To address these issues, the "Dokestrans" archiving system was developed as a comprehensive document management solution using the 4D methodology, which includes definition, design, development, and dissemination phases. The Dokestrans system streamlines document organization, provides graphical reports of documents collected per year or per element, and issues notifications for deficiencies in sub-elements, ensuring timely updates and compliance. Usability testing using the System Usability Scale (SUS) yielded an average score of 86, indicating excellent user satisfaction, while Blackbox testing confirmed the validity of all features. The implementation of Dokestrans significantly improves efficiency, accuracy, and organization in managing SMK PAU documents, contributing to enhanced safety management and operational effectiveness for public transportation companies.